Legal Enforcement of Local Election through Legal Sociology Approaches - Wagianto (International Journal of Psychosocial Rehabilitation, 2020)
Law enforcement in solving problems can be done with two approaches, namely litigation approach and non-litigation approach. It is chosen in order to fulfill the certainty and sense of legal justice in the community. One legal problem is the election dispute as happened in Lampung Province. This dispute is caused by allegations of fraud starting from the pre-campaign, the campaign period, the voting period, and the reporting period to the Lampung Province KPU. This study aimed to find the cause of the election dispute and its resolution with a sociological approach. This research was juridical by looking at facts in the field and then analyzed using descriptive analysis. There were several causes of the election dispute in Lampung, among others: (1). There was a cheating practice committed by one of the participants in the election or the winner of the election in Lampung according to the party that lost the election. (2). There was a presumption that there has been a practice of political money carried out by one of the pairs of governer candidate and vice governer candidate. There is an effort to enforce the law through a normative approach by 2 (two) pairs of governer candidate by submitting claims to the General Election Commison (KPU) even though there has been an act of resolution by KPU, but there are other parties two governer dan vice governer pairs were not satisfied and continue the resolution efforts to the Constitutional Court. Efforts to uphold the law through the approach of legal sociology was approaching the disputing parties with KPU mediation, Lampung Provincial government officials, religious leaders, and traditional leaders in Lampung in order to achieve peace.